Sistem Informasi Monitoring Barang Produksi Menggunakan Metode FIFO - M. Rizki Dwipa; Ade Supriatna; Dadang Latif (LPPM STMIK Mardira Indonesia, 2022)
Gold or aurum (Au) is a precious metal, because it is stable, does not change substances, does not oxidize in normal air, has stable properties, and is a pure element. In the current era, there are many companies in the jewelry sector that produce various processed products from gold, such as bracelets, rings, necklaces, etc. Given the importance of data collection for companies, it is necessary to monitor and collect data on production goods. In the face of developments in the modern era today requires a system to improve the quality of goods management. No PT. HARTADINATA ABADI TBK (HRTA) is engaged in manufacturing gold jewelry and jewelry. The company has a product marketing distribution network with wholesalers, retailers and own stores. Those who have data collection problems are still using the manual system. The author makes a web-based goods monitoring information system using qualitative descriptive analysis research methods. This type of research is generally used in social phenomenology. One of these social studies is related to guidance and counseling research. The system is made using the HTML, CSS, PHP, javascript and database programming languages using MYSQL, with the Object Oriented Software Engineering (OOSE) development method emphasizing use cases, so this system can be used to support the performance of the head of the polishing division and the polishing admin of the division.